2016
DOI: 10.21475/ajcs.2016.10.08.p7855
|View full text |Cite
|
Sign up to set email alerts
|

Cotton growth and yield dynamics across canopy layers in response to soil waterlogging

Abstract: Due to an indeterminate growth habit, we hypothesised that different canopy layers of cotton might be variably influenced by soil waterlogging. The field-grown cotton cultivar (Sicot 71BRF) was waterlogged at early (WL early , 77 days after planting [DAP]) and late reproductive phases (WL late , 101 DAP) for 120 h. Data from different canopy layers e.g. bottom eight (MSN 1-8 ), middle five (MSN 9-13 ), and upper five main stem nodes (MSN 14+ ) were collected 1 d (post-WL) and 7 d after termination of waterlogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A wealth of studies also reported that WL significantly affected the growth and development of cotton plants, including plant height, root length, and shoot and root biomass [ 6 , 15 , 22 , 23 , 34 , 42 ]. It has also been reported that the deleterious effect of WL led to late maturity, boll abscission, lower yield, and reduced fiber quality [ 21 , 23 , 29 , 37 , 38 , 39 , 43 , 44 , 45 , 46 ]. In fact, WL conditions create an imbalance between the production and consumption in plants’ carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies also reported that WL significantly affected the growth and development of cotton plants, including plant height, root length, and shoot and root biomass [ 6 , 15 , 22 , 23 , 34 , 42 ]. It has also been reported that the deleterious effect of WL led to late maturity, boll abscission, lower yield, and reduced fiber quality [ 21 , 23 , 29 , 37 , 38 , 39 , 43 , 44 , 45 , 46 ]. In fact, WL conditions create an imbalance between the production and consumption in plants’ carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20–50 mg fresh pollen grains or leaves were collected to measure total soluble sugars according to Yemm and Willis (1954) and our previous study (Najeeb, Tan, & Bange, 2016). Briefly, the samples were extracted in boiling 80% ethanol (2.5 ml) for 5 min and twice more in boiling distilled water followed by centrifugation at 4,500 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were then placed at 25 C to record initial electrolyte conductivity using Hanna conductivity meter (HI 98195,Hanna Instruments,Waltham). Final electrolyte conductivity was measured after boiling the samples at 100 C for 60 min and cooling to 25 C. RCI% was calculated according to Chauhan and Senboku (1996) with the following Approximately 20-50 mg fresh pollen grains or leaves were collected to measure total soluble sugars according to Yemm and Willis (1954) and our previous study (Najeeb, Tan, & Bange, 2016).…”
Section: Plant Materials and Stress Treatmentmentioning
confidence: 99%